2003
DOI: 10.1002/hpm.692
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial constraints and incentives on professional autonomy

Abstract: General practice has been the subject of extensive reforms over the 1990s in Australia as elsewhere. Reforms have attempted to improve quality and contain the overall cost of health care, and have often been seen as reducing the autonomy of medical professionals. This paper examines the impact of financial constraints and incentives introduced during the 1990s on Australian GPs' perceptions of autonomy. An existing seven component definition of autonomy and six themes that emerged from reviewing publications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Our study also found considerable overlap among consistent predictors (the ability to obtain high-quality services, the proportion of revenue from managed care, and the perceived complexity of care expected greater than it should be). Previous work found that perceived autonomy was related to financial autonomy, 14 discipline, 22 solo practice, 22 and managed care revenues, 24 perhaps because of the effect of incentives to reduce services. 8 Thus, these outcomes are related but not identical.…”
Section: Career Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also found considerable overlap among consistent predictors (the ability to obtain high-quality services, the proportion of revenue from managed care, and the perceived complexity of care expected greater than it should be). Previous work found that perceived autonomy was related to financial autonomy, 14 discipline, 22 solo practice, 22 and managed care revenues, 24 perhaps because of the effect of incentives to reduce services. 8 Thus, these outcomes are related but not identical.…”
Section: Career Satisfactionmentioning
confidence: 99%
“…9 -12 One explanation for diminishing satisfaction among PCPs may be a decreasing sense of professional autonomy. 13 PCPs are experiencing a loss of perceived autonomy, 14 possibly because of incentives designed to decrease services and expenses. 8 This decline in the sense of autonomy is greater among PCPs compared with specialists.…”
mentioning
confidence: 99%
“…Approximately 39% of the 508 responding PCPs said they would become surgical or diagnostic specialists, whereas approximately 22% said they would not choose medicine as a career. 23 In an attempt to shed some light on the declining level of satisfaction, 24 decreasing sense of professional autonomy, 25 and "feelings of powerlessness" 26 in the complex health care environment within which PCPs operate, 27 Katerndahl et al 28 used Community Tracking Survey data collected during 3 consecutive periods (ie, 1996 -1997, 1998 -1999, and 2000 -2001) to examine the relationships of both perceived autonomy and perceived complexity of care on PCPs career satisfaction. They concluded that there is considerable interaction between perceived complexity of care, perceived autonomy, and career satisfaction of PCPs.…”
mentioning
confidence: 99%
“…For example, where the service imposes no out-of-pocket payment on the patient, then the incentive for the doctor to suggest a follow-up visit may be increased. It should be noted however that patients have increasing access to health information on the Internet and that this is changing the relationship between the doctor and patient [13].…”
Section: Relationship Between Co-payments Demand Supply and Health mentioning
confidence: 98%
“…Lewis and Marjoribanks [13] comment on the distinction and divergence of views and interests between the macro level of the profession, represented by organised medicine and the micro level which is represented by individual doctors. They note that it is possible that policies agreed to by the professional bodies can enhance some aspects of the profession but may diminish aspects at the micro level.…”
Section: Reasons For the Fall In Gp Bulk Billingmentioning
confidence: 99%